Identification and characterization of tertiary lymphoid structures in brain metastases - Sadaf S. Mughal; Yvonne Reiss; Jörg Felsberg; Lasse Meyer; Jadranka Macas; Silja Schlue; Tatjana Starzetz; Karl Köhrer; Tanja Fehm; Volkmar Müller; Katrin Lamszus; Dirk Schadendorf; et al. (Acta Neuropathologica Communications)
Abstract Brain metastases (BrM) are the most common cancers in the brain and linked to poor prognosis. Given the high incidence and often limited treatment options, understanding the complexity of the BrM tumor microenvironment is crucial for the development of novel therapeutic strategies. We performed transcriptome-wide gene expression profiling combined with spatial immune cell profiling to characterize the tumor immune microenvironment in 95 patients with BrM from different primary tumors. We found that BrM from lung carcinoma and malignant melanoma showed overall higher immune cell infiltration as compared to BrM from breast carcinoma. RNA sequencing-based immune cell deconvolution revealed gene expression signatures indicative of tertiary lymphoid structures (TLS) in subsets of BrM, mostly from lung cancer and melanoma. This finding was corroborated by multiplex immunofluorescence staining of immune cells in BrM tissue sections. Detection of TLS signatures was more common in treatment-naïve BrM and associated with prolonged survival after BrM diagnosis in lung cancer patients. Our findings highlight the cellular diversity of the tumor immune microenvironment in BrM of different cancer types and suggest a role of TLS formation for BrM patient outcome.